(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The article examines modern trends and features of digitalization processes in the economy of Azerbaijan. The state policy on the active digitalization of economic relations has found its expression in the state programs “Azerbaijan 2030: National Priorities for Socio-Economic Development” and “Socio-Economic Development Strategy for 2022‒2026”, which contain serious tasks in the direction of the digital transformation of the economy and society. The provisions of these programs are examined in the article. The result of the analysis was the determination of the trend that digital technologies are widely used in Azerbaijan today, and the country is already on the path of digital transformation, and, as in developed countries, digitalization of the economy and the introduction of innovations are priorities in Azerbaijan. Keywords: digital economy; digitalization; digital imperative; e-government; innovation; high technologies.